Frizzled receptors: gatekeepers of Wnt signaling in development and disease - Martinez-Marin, Dalia; Stroman, Grace C.; Fulton, Camryn J.; Pruitt, Kevin (Frontiers in Cell and Developmental Biology, 2025)
Frizzled (FZD) receptors are a subset of G-protein-coupled receptors (GPCRs), the largest class of human cell surface receptors and a major target of FDA-approved drugs. Activated by Wnt ligands, FZDs regulate key cellular processes such as proliferation, differentiation, and polarity, positioning them at the intersection of developmental biology and disease, including cancer. Despite their significance, FZD signaling remains incompletely understood, particularly in distinguishing receptor-specific roles across canonical and non-canonical Wnt pathways. Challenges include defining ligand-receptor specificity, elucidating signal transduction mechanisms, and understanding the influence of post translational modifications and the cellular context. Structural dynamics, receptor trafficking, and non-canonical signaling contributions also remain areas of active investigation. Recent advances in structural biology, transcriptomics, and functional genomics are beginning to address these gaps, while emerging therapeutic approaches—such as small-molecule modulators and antibodies—highlight the potential of FZDs as drug targets. This review synthesizes current insights into FZD receptor biology, examines ongoing controversies, and outlines promising directions for future research and therapeutic development.